New free-range European bison herd in Zachodniopomorskie voivodship one year after creation (European Bison Conservation Newsletter, 2009)
Two free-range European bison herds were established in 2008 in Forest Districts Łobez and Dobrzany at a distance of 14 km from each other. After 10 months being separated those herds have merged into one group and occupied the poor wood habitat in the Drava River sandur valley. Those herds left the area of the reach forest habitat of In´ skie Lakeland. The reproduction was very good because among 7 cows probably 5 calves were born and at least three of them survived first 3 months. The monitoring was very hard because of low quality equipment – the Vectronic Aerospace GPS telemetry collars, which operated an average for 4 months from recommended period of 2 years.
Keywords: free ranging herds; GPS collars